2015
DOI: 10.16925/od.v11i21.950
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia y distribución de hábitos parafuncionales en un grupo de escolares mexicanos, 2014

Abstract: Cómo citar este artículo: Murrieta-Prudena JF, Martínez-Hernández L, Morales-Vázquez J, Linares-Vieyra C, González-Guevara MB. Frecuencia y distribución de hábitos parafuncionales en un grupo de escolares mexicanos, 2014. Rev Nac Odontol. 2015;11(21):57-64. doi: http://dx.doi.org/10. 16925/od.v11i21.950 Resumen. Introducción: un hábito parafuncional es el resultado de la perversión de una función normal que se adquiere por la práctica repetida de un acto que no es necesario en cavidad bucal. El presente est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…This study also showed that the risk of midline deviation increases in children with non-nutritive habits according with Mesquita [12] who found pacifier sucking habit increase the risk of midline deviation. On the other hand, the frequency of oral breathing in the present work was higher (22%), with respect to the use of pacifier (14%), similar result obtained by the research of Accardi [10] and Murrieta-Prudena., et al [15] where the use of the pacifier also showed a low percentage and no percentage respectively. Finding a statistically significant relationship between the different types of breathing presented and the deep palate, similar to the study conducted by Diaz [16].…”
Section: Resultsmentioning
confidence: 94%
“…This study also showed that the risk of midline deviation increases in children with non-nutritive habits according with Mesquita [12] who found pacifier sucking habit increase the risk of midline deviation. On the other hand, the frequency of oral breathing in the present work was higher (22%), with respect to the use of pacifier (14%), similar result obtained by the research of Accardi [10] and Murrieta-Prudena., et al [15] where the use of the pacifier also showed a low percentage and no percentage respectively. Finding a statistically significant relationship between the different types of breathing presented and the deep palate, similar to the study conducted by Diaz [16].…”
Section: Resultsmentioning
confidence: 94%
“…Por otro lado cabe recalcar que de los datos analizados no se obtuvieron resultados estadísticamente significativos en cuanto al sexo y la prevalencia de hábitos orales parafuncionales (Cepero Sánchez et al;Reyes Romagosa et al;Murrieta Pruneda et al, 2015;Carrillo Valencia et al, 2016;Espinoza Calle et al, 2016;.…”
Section: Discussionunclassified
“…En las dos ciudades, los niños entre 10 y 12 años de edad presentaron mayor frecuencia de onicofagia, lo cual es consistente con lo expresado por Murrieta et al [18] y Tanaka et al [19], quienes refieren la onicofagia como el hábito oral más frecuente, probablemente debido al hecho de que este hábito puede ser transferencia de los hábitos de succión, que tienden a ser abandonados durante el tercer año de vida cuando comienza la onicofagia; mientras que el hábito de biberón tuvo mayor frecuencia en los pacientes entre 4 y 6 años en ambas ciudades.…”
Section: Hábitos Bucales Medellínunclassified